Drug-induced cataract: a real-world study based on the food and drug administration adverse event reporting system database - Cao, Xianfen; Zhou, Xiaoping; Wu, Shinan; Zeng, Jing; Ou, Yulun; Zhou, Qing (Frontiers in Medicine, 2026)
PurposeThis study aims to investigate the risk of drug-induced cataract and examine its epidemiological patterns using real-world data.MethodsData from the FDA Adverse Event Reporting System (FAERS), spanning January 2004 to December 2024, were analyzed. A disproportionality analysis was conducted on the FAERS database using four quantitative measures—reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS)—to identify potential safety signals. The study categorized the identified cataract-induced drugs by risk level and quantitatively compared the time to onset across these categories.ResultsA total of 671 drugs were reported to be associated with cataract in the FAERS database. Disproportionality analysis identified 64 drugs with a significant risk of cataract formation. The primary therapeutic classes included hormonal, oncological, and ophthalmic medications, along with drugs acting on the nervous system. The highest-risk drugs identified were omidenepag isopropyl, clobazam, and nitisinone, with BCPNN scores of 7.69, 7.36, and 6.02, respectively. Ophthalmic medications showed the shortest mean onset time for drug-induced cataract, averaging 120.29 days. The majority of affected individuals were female (67.59%) and elderly (mean age 63.85 ± 14.54 years).ConclusionThis study provides real-world evidence regarding the risk of drug-induced cataract, offering empirical support for preventive strategies and informed clinical decision-making.